Analisa Neraca Air Permukaan Das Renggung Untuk Memenuhi Kebutuhan Air Irigasi Dan Domestik Penduduk Kabupaten Lombok Tengah - Zulkipli, Zulkipli; Soetopo, Widandi; Prasetijo, Hari (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2012)
Research attempts to understand the potential and demand of water and the water balance, the review on water balance at Watershed Renggung to ensure the satisfaction of the demand of irrigation and domestic waters at Central Lombok District. In this research water potential is 243.34 millions m3 comprising to 22.59 millions m3 river water, 252.51 millions m3 HLD supplement, and 1,309 mm rainfall or equaled to 252.51 millions m3. River water supply is calculated based on 80 % (Q80) dependable discharge from AWLR Renggung- Ponggong in the period from 1992 to 2011. Discharge is used as the guidance to determine water availability at Watershed Renggung. Result of analysis indicates that the maximum discharge is available at 3.658 m3/ second on March. The average debit is 0.721 m3/second, while the minimum discharge is 0.608 m3/second on October. The current water demand for multi-sectors is 225.11 millions m3. These multi-sectors include domestic, irrigation, animal husbandry, fishery and industry. For the industry, the water is supplied only to the industry in the sub-district at the Watershed. The analysis devices for water availability involve the analysis of rainfall and the analysis of surface water.The water demand total at Watershed Renggung for the next 25 years is estimated in the average as 227.58 millions m3. This total figure consists of: 208.40 millions m3 for irrigation water, 7.59 millions m3 for domestic water, 5.40 millions m3 for animal husbandry, 4.90 millions m3 for fishery, and 1.30 millions m3 for industry. The prediction of water demand total from 2011 to 2031 based on Water Demand Index (IKA) Standard of NSAD at NTB Province is 94.75 % in average, meaning that the water use rate is critical. By 2036, IKA is assumed as 101.87 meaning that the water use rate will be deficit.Keywords: water demand, water availability, water balance